Tumor Kelenjar Parotis - Intan Zuryani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
This study is to find out about Parotid Gland Tumors, Salivary Gland Physiology, Definition of Parotid Tumors, Epidemiology, Etiology, Classification, Benign Parotid Tumors, Malignant Parotid Tumors, Clinical Manifestations, Diagnosis, Supporting Examinations, Therapy, Complications and Prognosis. Parotid tumors are tumors that attack the parotid salivary glands. The etiology of salivary gland tumors remains unknown but a multifactorial role is thought to be involved. The most common benign salivary gland tumor in children is parotid gland hemangioma. In adults, benign salivary gland tumors that often occur include pleiomorphic adenomas. Parotid malignant tumors in children are rare and the most common in children is mucoepidermoid carcinoma. The diagnosis of a parotid gland tumor will depend on the history, clinical examination, imaging, and fine needle aspiration biopsy (FNAB). Treatment of parotid tumors is based on appropriate staging and preoperative diagnosis. Facial nerve injuries and Frey's Syndrome are complications that often arise. Most salivary gland tumors are non-malignant and grow slowly. Surgical removal of the tumor usually cures the patient.